PENYELESAIAN SENGKETA DI PENGADILAN DALAM PERMA NOMOR 1 TAHUN 2016 TENTANG MEDIASI - Muhammad Abduh (Ahwaluna | Jurnal Hukum Keluarga Islam, 2022)
Settlement of disputes through mediation is preceded by a discussion of negotiations as the basis for the procedure for resolving disputes through mediation because in mediation efforts to resolve disputes are carried out through negotiation and bargaining between the disputing parties. This research can be categorized as literature research, the theoretical framework of the normative - juridical approach. In an effort to find the truth, the authors use a normative - juridical approach. The technique used is the main content analysis related to mediation in Perma No. 1 of 2016. The results of this study are as follows. First, the mediator certificate is explained in Perma Number 1 of 2016 Article 13 that every mediator is required to have a mediator certificate obtained after participating and declared to have passed the mediator certification training organized by the Supreme Court or an institution that has obtained accreditation from the Supreme Court. Second, the mediation procedure in the Supreme Court regulations applies in a litigation process in court, both within the General Court and Religious Courts. Each judge, mediator, parties and/or legal counsel must follow the procedure for resolving disputes through mediation.